Inclusive designed cities: how can inclusive design create a more inclusive city by using transit oriented development principles? - Slabbert, Rochelle (My University, 2020)
This research sets out to describe how inclusive design can create a more inclusive city by using transit oriented development principles. The World Urbanization Prospects of 2018 states that currently 55% of the world’s population resides in urban areas, which is expected to increase to 68% by 2050. Urbanisation has been a major challenge and has had a major effect on Johannesburg and its built form, with a large number of the population having to live on the fringes of the urban development boundary. Sprawling has taken place and as a result people are separated from their place of work. Inclusive design is the complete opposite of such a scenario where connectivity and accessibility are seen as important factors for an inclusive urban environment, including access to public transport facilities so that people are not “cut off” from the vital social benefits of living within a community. With inclusive designs significant focus towards public transport, the notion of Transit Oriented Developments (TOD’s) has been identified as a potential opportunity to create a more inclusive city. TOD’s act as a solution for communities to provide them with access to transport facilities, amenities, economic activities, high quality spaces and affordable accommodation. TOD’s have also been identified as a “key aspect” of the compact polycentric vision for Johannesburg to address the issue of the sprawling city. Although accessibility; affordability, resilience and sustainability are of equal importance to inclusive designed environments, accessibility has largely been neglected in inclusive designed environments. Accessibility is mostly viewed as access to public transport facilities and while various theories and components exist for the development of TOD’s inclusive designed environments, there is an evident gap for research that could potentially act as a means to inform and promote policy development and enable developing countries to gain a much broader understanding of how to design cities that are inclusive. In this study, Frankenwald in Johannesburg is selected as a case study due to its proximity in terms of public and private transport routes. The case study will explore TOD principles as informative for an inclusive designed environment. The expected findings for the research is that it could potentially address the vision of the Johannesburg’s urban future by contributing towards a more sustainable, inclusive and equitable environment. Lastly, to understand what the current separators are that separate people from their place of work and home from an inclusionary design perspective.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirement for the degree of Master of Urban Design, Johannesburg 2020